Spatial variation in autism in Baghdad, 2024 (Journal of the College of Basic Education, 2025)
The research addressed a complex and difficult disease characterized by mental, psychological, and behavioral disorders that afflict children at a young age: autism. Its symptoms appear before the age of three and can sometimes persist for life if treated early. This disease is linked to the development of a child's brain and how they distinguish objects and people in their surrounding environment, which leads to increased risk of developing autism. The research problem came to identify one of the most important and dangerous pathological phenomena, which is autism in young children. Then the research hypothesis was represented by identifying the concept of autism and identifying the problems and obstacles that those afflicted suffer from, including their acquisition of customs and traditions in their daily behavior, whether with the environment surrounding them, represented by their families or with society. It relied on the objective approach and the analytical approach to show the geographical distribution of autism in the city of2024. It causes health and mental problems affecting language, behavioral, and developmental skills. The disease is the result of multiple factors and causes—pathological, genetic, environmental, viral, and behavioral—that interact to play a significant and fundamental role in its development. The study examined the geographical distribution of autism in Baghdad. The researcher relied on fieldwork to achieve the research objectives and requirements, reaching multiple conclusions, the most important of which was identifying the factors that cause autism. Among children, the most important factor is the genetic factor. The study indicated the geographical distribution of autism in the city of Baghdad in 2024. The researcher hopes that this topic will constitute an incentive and motivation for future studies that will receive wide attention from specialists and relevant parties to exert more efforts and develop development strategies for treatment and the necessary to improve the reality of this segment of the community.